Green and simple extraction of free seleno-amino acids from powdered and lyophilized milk samples with natural deep eutectic solvents - López, Romina Vanesa (2020)
Natural deep eutectic solvents (NADES) were introduced for the extraction of free seleno-amino acids from lyophilized and powdered milk samples. Different NADES were evaluated, and lactic acid:glucose (LGH) showed the highest selenium recoveries. Selenium analysis was performed by inductively coupled plasma mass spectrometry (ICP MS). Se-NADES analysis in ICP MS was optimized according to the radio frequency power and nebulization gas flow rate. Se-NADES extraction was optimized by an experimental design. LGH dilution, LGH volume, sample quantity, and ultrasound time were factors influencing the extraction. Seleno-amino acids were determined by liquid chromatography-ICP MS. After optimization, the limits of detection obtained were 7.37, 8.63, and 9.64 µg kg−1 for selenocysteine, selenomethionine, and seleno-methyl-selenocysteine, respectively. The NADES-extraction is a green procedure with 2 penalty points in the EcoScale. The method was applied to the analysis of powdered milk, lyophilized Se-fortified sheep milk, and ERM-BD151 skimmed milk powder.